Lessons from local governance and collective action efforts to manage irrigation withdrawals in Kansas - Perez-Quesada, Gabriela; Hendricks, Nathan P. (My University, 2021)
This study evaluates four groundwater management plans to increase the understanding of how local governance and collective action can be effectively implemented to manage irrigation withdrawals in Kansas. The results of our analysis demonstrate five key lessons that highlight the challenges of collective action efforts to manage common-pool resources in a developed country setting. First, the four management plans generally follow Ostrom’s design principles for collective action. However, there are important areas—particularly boundaries and allocations definition—where the management plans could be improved to better align with Ostrom’s design principles. Second, a majority of farmers agree that action is needed to reduce the rate of aquifer depletion but management plans have not substantially reduced water use. Third, management plans that allow for voluntary participation have not received more support than those that require mandatory compliance, perhaps due to the classic free-rider problem. Fourth, there is no clear evidence that heterogeneous benefits from management explain support within a management area. Fifth, groundwater users generally perceive that they have an acceptable level of information. Our analysis highlights the significant challenges facing successful collective action efforts to manage water in the USA. and that the efforts are most likely to be successful when they are small-scale, mandatory, and involve users in the formation process.
Keywords: Ogallala aquifer; Collective action; Local governance; Irrigation; Aquifer depletion